Determinants of Sharia digital gold investment intention among Jabodetabek Muslim youth - Luthfi, Anindita Almira; Hati , Sri Rahayu Hijrah (Faculty of Business & Economics, Universitas Islam Indonesia, 2025)
Purpose – This study aims to identify and analyze the primary factors that shape or drive investment intentions of Muslim youth in the Jabodetabek region toward Sharia-compliant digital gold platforms.Methodology – Using a sample of 237 Muslim respondents from Generation Y and Z, data were examined using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the relationships among the proposed constructs.Findings – The results reveal that trust exerts a positive effect on user attitudes, whereas risk has an adverse impact. Both perceived financial health and perceived innovativeness significantly enhanced attitudes, indicating that users with stable financial conditions and openness to innovation are more receptive to such investments. Although perceived ease of use significantly influences perceived usefulness, neither construct directly affects attitudes. Importantly, attitude emerged as the strongest predictor of behavioral intention to invest in Sharia digital gold among the target demographics.Implications – Focusing on Sharia digital gold as a specific investment avenue, this study adds to the existing body of knowledge by analyzing how perceived trust, innovativeness, financial health, risk, usefulness, and ease of use affect investment intentions, with attitude acting as a key mediating factor.Originality – This research extends traditional technology acceptance frameworks by incorporating financial health and perceived innovativeness, offering fresh insights into Islamic fintech adoption among Gen Y and Z members in Jabodetabek. It offers a more in-depth insight into behavioral intention inside a growing segment of ethical, digital-savvy investors in a Muslim-majority context.